Oil consumption and growth: Is there a threshold effect of greenhouse gases emissions - Sarah Nandnaba; Abebe Hailemariam; Rangan Gupta; Xin Sheng (Innovation and Green Development)
The paper empirically examines the threshold effect of GHG(s) emissions on the oil consumption-growth nexus. Using a nonlinear local projection approach and an extended historical dataset from 1890 to 2022, we find that the impact of oil consumption on economic growth is conditional on the level of GHG(s) emissions. More specifically, we find that economies in high-emission regimes face a slowdown in growth while those in low-emission regimes benefit from a positive shock in oil. The results have important policy implications for sustainable growth.